Odatix: An open-source design automation toolbox for FPGA/ASIC implementation - Jonathan Saussereau; Christophe Jego; Camille Leroux; Jean-Baptiste Begueret (SoftwareX)
In modern hardware digital design, optimizing performance, resource utilization, and power consumption across different technological targets remains a critical challenge. Indeed, the drive for greater computational power, alongside the need to reduce power consumption, stems from a wide range of applications, from data centers to mobile devices. However, this push encounters significant cost barriers, as the manufacturing cost is closely tied to the technological nodes used and the area for integrated circuits, and is particularly influenced by the amount of available resources for FPGAs. These three criteria are inherently conflicting, as improving one often negatively impacts the others. Finding the best balance between these factors requires significant effort. To address these complexities, design automation tools are increasingly valuable. Odatix is an open-source toolbox designed for the automated implementation and validation of parametrizable digital architectures. It supports synthesis, placement and routing for various FPGA and ASIC tools and simulators. It simplifies key stages such as synthesis, place and route, simulation, and validation, allowing designers to efficiently navigate multiple configurations and identify optimal solutions tailored to specific application constraints. Indeed, Odatix enables comparative analysis of multiple architectural configurations through various metrics such as maximum operating frequency, resource utilization, and power consumption. This paper presents an overview of Odatix’s capabilities and its application to the AsteRISC processor, demonstrating its utility in choosing the best architectural configuration, technological target and EDA tool for specific application constraints.